The importance of return to work: How to achieve optimal reintegration in ACS patients. (29th August 2020) - Reibis, Rona; Salzwedel, Annett; Abreu, Ana; Corra, Ugo; Davos, Constantinos; Doehner, Wolfram; Doherty, Patrick; Frederix, Ines; Hansen, Dominique; Christine Iliou, Marie; Vigorito, Carlo; Völler, Heinz; et al.
Abstract: The vocational reintegration of patients after an acute coronary syndrome is a crucial step towards complete convalescence from the social as well as the individual point of view. Return to work rates are determined by medical parameters such as left ventricular function, residual ischaemia and heart rhythm stability, as well as by occupational requirement profile such as blue or white collar work, night shifts and the ability to commute (which is, in part, determined by physical fitness). Psychosocial factors including depression, self-perceived health situation and pre-existing cognitive impairment determine the reintegration rate to a significant extent. Patients at risk of poor vocational outcomes should be identified in the early period of rehabilitation to avoid a reintegration failure and to prevent socio-professional exclusion with adverse psychological and financial consequences. A comprehensive healthcare pathway of acute coronary syndrome patients is initiated by cardiac rehabilitation, which includes specific algorithms and assessment tools for risk stratification and occupational restitution. As the first in its kind, this review addresses determinants and legal aspects of reintegration of patients experiencing an acute coronary syndrome, and offers practical advice on reintegration strategies particularly for vulnerable patients. It presents different approaches and scientific findings in the European countries and serves as a recommendation for action.